2007
DOI: 10.1051/0004-6361:20066401
|View full text |Cite
|
Sign up to set email alerts
|

Spectral atlas of massive stars around $\ion{He}{i}$ 10 830 Å

Abstract: We present a digital atlas of peculiar, high-luminosity massive stars in the near-infrared region (10 470−11 000 Å) at medium resolution (R 7000). The spectra are centered around He i 10 830 Å, which is formed in the wind of those stars, and is a crucial line to obtain their physical parameters. The instrumental configuration also sampled a rich variety of emission lines of Fe ii, Mg ii, C i, N i, and Pa γ. Secure identifications for most spectral lines are given, based on synthetic atmosphere models calculate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 97 publications
9
71
1
1
Order By: Relevance
“…In addition, Machado et al (2004) using high resolution spectra confirmed the binarity and intrinsic variability of GG Car. Groh et al (2007) detected Paγ and HeI 10830 Å in emission along with several features produced by FeII, MgII, and CI in its nearinfrared spectrum. In addition, GG Car appears to display 13 CO band emission in its mid-infrared spectrum, indicating that it is indeed a sgB[e] star (Kraus 2009) based on the enrichment of its circumstellar matter by 13 C.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, Machado et al (2004) using high resolution spectra confirmed the binarity and intrinsic variability of GG Car. Groh et al (2007) detected Paγ and HeI 10830 Å in emission along with several features produced by FeII, MgII, and CI in its nearinfrared spectrum. In addition, GG Car appears to display 13 CO band emission in its mid-infrared spectrum, indicating that it is indeed a sgB[e] star (Kraus 2009) based on the enrichment of its circumstellar matter by 13 C.…”
Section: Introductionmentioning
confidence: 95%
“…Koen & Eyer (2002) also reported a signal 0.16 c/d (or 6.18 days) in their analyses of the Hipparcos data. Also, some authors (Groh et al 2007) argue that this object is in fact a binary star, as has been proposed recently for other Be stars such as Achernar (Kervella et al 2008). On the other hand, Eggleton & Tokovinin (2008) flag the star as a single object, and Lefèvre et al (2009) point to it as an irregular variable star.…”
Section: Discussionmentioning
confidence: 64%
“…Later on, the star reached an almost quiescent phase in 2000, and again entered an active phase in 2001. Recently, Groh et al (2007) pointed out an X-ray source near λ Pav and suggest there is a binary companion as a possible scenario. Again, the natural limitations in our time sample, made it impossible to ascribe a signal related to binarity, and also it is unlikely that ν 1 arise from that since it would lead to a very short period, which is typical of Algol-type stars.…”
Section: Time Series Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Its morphology ranges from an absorption line in stars with low density winds to a broad P-Cygni profile in Wolf-Rayet stars 1,2 . In some cases, the emission part of the P-Cygni profile is flat-topped, in other cases it is rounded or strongly peaked 3 . Whatever the morphology, it is related to the velocity law in the wind and can thus provide unique information.…”
Section: Astrophysical Backgroundmentioning
confidence: 99%